2019
DOI: 10.33854/heme.v1i2.238
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Tingkat Stres pada Mahasiswa Angkatan 2018 dengan Angkatan 2015 Fakultas Kedokteran Universitas Baiturrahmah

Abstract: Stress in college students have negative impacts to their lectures and performance. The aim was to determine comparison of stress level in medical college of 2018 with 2015 in medical faculty of Baiturrahmah University. This  research  was  cross  sectional study, observational unpaired  categorical  comparative  analytics. The participants were 80 peoples. Stress was assessed by using Perceived Stress Scale (PSS-10). Data obtained was tabulated and analyzed using chi-square. The result, The medical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
2
8
0
10
Order By: Relevance
“…Based on the results of these measurements, it can be seen that the medical students at Nusa Cendana University dominate with moderate stress levels and the initial stress level is lower than with students in the last semester. This is in line with previous studies by Agusmar et al (2019) which found that medical students' stress level in the 2015 class was higher than that of 2018. It has been explained that the factors causing stress in final students are failing to adapt, accumulation of college burdens, and finance factors, relationships to friends, partners, future careers, and a lack of time management.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of these measurements, it can be seen that the medical students at Nusa Cendana University dominate with moderate stress levels and the initial stress level is lower than with students in the last semester. This is in line with previous studies by Agusmar et al (2019) which found that medical students' stress level in the 2015 class was higher than that of 2018. It has been explained that the factors causing stress in final students are failing to adapt, accumulation of college burdens, and finance factors, relationships to friends, partners, future careers, and a lack of time management.…”
Section: Discussionsupporting
confidence: 93%
“…Based on research conducted by Amallia [29] that there are 152 students in the moderate stress category with a percentage of 37.7% in the first year and 61.2% in the final year. The results of the research above are also in line with research conducted by Agusmar [1] that final year students experience moderate stress by 87.5% than first batch students. This increased stress, if not handled and controlled properly, can make stress uncontrollable and can cause physical and psychological impacts that can disrupt the lives of final year students [8].…”
Section: Introductionsupporting
confidence: 89%
“…Factors that can cause a state of stress on students at the end of them because it felt like a failure in self-adjustment, college expenses are piling up, economic factors, a relationship friend/spouse, a career in the future, and the lack of time management. While at the level of the student's initial experience of stress can occur due to a change adaptation time from school to the university, where to stay far away from parents and the environment that are less good (10).…”
Section: The Stress Level Of Respondentsmentioning
confidence: 99%